Four weddings and a puppy - Shane, Lizzie (Shane, Lizzie. Pine Hollow series, 2024)
"Kendall Walsh has exactly one second to save a fancy, five-tiered wedding cake and any possibility of being a wedding planner--not to mention her family's struggling ski resort. All because of one very cute, very furry, golden menace of a retriever who has a serious thing for butter chiffon icing. Which is exactly when Olympic skier Brody James shows up and saves the day . . . and the cake. Brody makes Kendall feel about a million indecipherable things. He's her brother's bestie. Her first crush. And a ridiculously popular Olympic hero, which only reminds her of her own failed Olympic dreams. What Brody isn't telling her is that he's walked away from it all. The fame. The sponsorships. The celebrity girlfriend. Now he and Kendall are both lost somewhere between their past and a future they can't yet see. But four weddings, one mischievous puppy, and a few steamy kisses later, these two might just realize that they are both exactly where they need to be...with each other."--